Implementasi Kebijakan Siaga SAR Pada Periode Natal dan Tahun Baru: Studi Kasus Kantor Pencarian dan Pertolongan Yogyakarta - Rosali, Rusy; Saharuddin, Erni (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2026)
The increasing public mobility during the Christmas and New Year holidays requires well-planned SAR preparedness. This study aims to describe the organization and governance of search and rescue (SAR) operations during the Special Christmas and New Year Alert at the Yogyakarta Search and Rescue Office. A qualitative descriptive method was employed through in-depth interviews with the subsection head, radio operators, BPBD officers, police, and community members, complemented by field observations. The findings indicate that the alert operations were systematically arranged through inter-agency coordination, risk-based planning using historical accident data, and the strategic placement of posts and personnel according to hazard levels. Radio operators played a crucial role in bridging information between the field and the command center. Community involvement in reporting and volunteering also accelerated incident response. Theoretically, this study strengthens the application of Edward III’s management functions in disaster management, particularly planning, coordination, directing, and controlling. Practically, it recommends enhancing human resource capacity, updating communication technologies, and reinforcing public education to optimize SAR operations in the future.